Enhancement of electron hot spot relaxation in photoexcited plasmonic structures by thermal diffusion - Spitzer, F; Glavin, B A; Belotelov, V I; Vondran, J; Akimov, I A; Kasture, S; Achanta, V G; Yakovlev, D R; Bayer, M (arXiv.org, 2016)
We demonstrate that in confined plasmonic metal structures subject to ultra-fast laser excitation electron thermal diffusion can provide relaxation faster than the energy transfer to the lattice. This relaxation occurs due to excitation of nanometer-sized hot spots in the confined structure and the sensitivity of its optical parameters to the perturbation in these regions. Both factors become essential when the plasmonic resonance condition is met for both excitation and detection. A pump-probe experiment on plasmonic gold lattices shows sub-picosecond relaxation with the characteristic times well-described by a two-temperature model. The results suggest that dynamical optical response in plasmonic structures can be tuned by selection of the structural geometry as well as the choice of wavelength and polarization of the excitation and detection light.